1980
DOI: 10.1029/jb085ib02p00925
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic P and S wave attenuation in dry and saturated rocks under pressure

Abstract: Ultrasonic P and S wave Q values as functions of hydrostatic pressure are presented for the Berea and Navajo sandstones, Bedford limestone, and Colorado oil shale. In most cases the attenuation was obtained for both dry and water‐saturated samples. Q is determined by measuring the attenuation of the rock sample relative to a high Q standard of identical geometry using Fourier spectral ratios. The data show that Q increases with pressure, the rate of increase being dependent on rock type and crack density and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(91 citation statements)
references
References 39 publications
2
89
0
Order By: Relevance
“…Since no core taken in a vertical direction is currently available, this conclusion has not been confirmed experimentally. In due course the digitized waveforms will be subjected to FFT's and Q-values calculated for the rock samples by a spectral ratio's technique such as that described by Johnston and Toksoz (1980). The velocity and frequency data correspond to a model of a jointed rock mass in which the joints intersected in the vertical direction are fewer and probably tighter than those intersected in the horizontal direction.…”
Section: Methodsmentioning
confidence: 99%
“…Since no core taken in a vertical direction is currently available, this conclusion has not been confirmed experimentally. In due course the digitized waveforms will be subjected to FFT's and Q-values calculated for the rock samples by a spectral ratio's technique such as that described by Johnston and Toksoz (1980). The velocity and frequency data correspond to a model of a jointed rock mass in which the joints intersected in the vertical direction are fewer and probably tighter than those intersected in the horizontal direction.…”
Section: Methodsmentioning
confidence: 99%
“…This relative rareness is partly due to: (i) the inherent difficulty of transmitting transducer signals through the waterproof pressure chamber in a loading apparatus ; and, on the other hand, (ii) the specificities in preparing and handling shale samples for mechanical testing (chemical sensitivity to water, extremely low permeability...). Most of the dynamic experimental studies reported in the literature on shale samples were performed under hydrostatic loading conditions (Johnston and Toksöz 1980;Jones and Wang 1981;Lo et al 1986;Johnston and Christensen 1995;Hornby 1998;Stanley and Christensen 2001). Only Yin (1992) carried out triaxial tests.…”
Section: Shale Lithologiesmentioning
confidence: 99%
“…Going from air-dry to fully fluid saturated case, attenuation increases (Johnston et al, 1980;Toksoz et al, 1979;Winkler and Nur, 1979). The largest effect of saturation occurs in Qs' In the air-dry case Q p '" Q s and, in fully saturated case Q s < Qp' Partial saturation may reduce Q p relative to full saturation, but this effect is generally small (Winkler and Nur, 1979;Johnston and Toksoz, 1980;Frisillo and Stewart, 1 980).…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of pore fluid to attenuation in rocks has been a subject of interest and intensive study (Bulau et al, 1984;Murphy, 1982;Spencer, 1981;Winkler and Nur, 1979;Mavko and Nur, 1979;Johnston et al, 1979;Johnston and Toksoz, 1980;O'Connell and Budiansky, 1977;Biot, 1956a,b;Wyllie et al, 1962).…”
Section: Introductionmentioning
confidence: 99%